Extraction Optimization of Phenolic Antioxidants from microwave treated Nelumbo nucifera Seed Flour - Nawaz, Haq; Shad, Muhammad Aslam; Abbasi, Sabiha Tahir (Free Radicals and Antioxidants)
Background: Nelumbo nucifera seeds are medicinally important due to the presence of phytochemicals with strong antioxidant potential. Extraction of these phytochemicals has been a major problem faced by the researchers. Objective: The purpose of the study was to optimize the process conditions for extraction of phenolic antioxidants from N. nucifera seed. Methods: Process variables for microwave assisted extraction of phenolic antioxidants from N. nucifera seed flour were optimized by response surface methodology using a multi-factorial central composite design based on five levels of each of four input variables including X1: particle size (in terms of mesh No.), X2: microwave treatment period (MTP), X3: solvent concentration (SC) and X4: extraction period (EP). Total extract yield was calculated as Total extractable components (TEC) and the extracts were analyzed for total phenolic content (TPC) and total antioxidant activity (TAOA). Results: Data analysis showed a significant increase (p<0.05) in TEC, TPC and TAOA in response to increase in the levels of selected factors. Optimum levels of extraction variables to achieve maximum level of response parameters were found to be: 125.96, 2.45 min, 55.21% and 3.87 h for TEC, 61.73, 1.66 min, 80.08% and 4.98 h for TPC and 60.89, 2.37 min, 44.98% and 1.123 h for TAOA. Conclusion: The extraction of phenolic antioxidants from N. nucifera seed flour is significantly increased in response to an increase in mesh No. (decrease in particle size), MTP, SC and EP but up to a certain limit. The decrease in extraction yield and antioxidant activity at higher levels of studied factors may be attributed to the possible decomposition of phenolic compounds due to prolonged duration of microwave heating and prolonged extraction time.
Keywords: Nelumbo nucifera seed flour; Microwave assisted extraction; Antioxidant activity; Response surface methodology; Central composite design; Phenolic content